Avaliação da fadiga em operadores de salas de controles de subestações elétricas. - Oliveira, Ana Maria Braga de (2009)
The operator of the control room of electrical substation main task is to keep the parameters of normality, making decisions and processing information. The present study had as objective to evaluate the perception of fatigue in the control room operators of electric substations. Thus, there was a descriptive study of cross-cohort, whose results were submitted to quantitative analysis, using the program SPSS, version 10. Developed in electric power substations located in the states of Paraíba and Ceará, had population of 37 operators and sample 33 (89,19%). For objectives collection was used the NASA-TLX questionnaire, as well as specific questionnaires. All participants were male, mean age of 42,42 years. Additionally, 78,8% of the sample are married and 45,5% have incomplete higher education. The time in which officials are in the company ranged from 3 to 33 years ( X = 17,02 years, SD = 11,02). The substations adopt in its operation rotating shift schedules. Most operators studied do not smoke, no do physical activity, being above ideal weight. Almost half the sample ingests alcohol regularly, with an average consumption of twice a week. Areas with considerable degree of discomfort felt during the working day were spine, wrists and hands. Fatigue was assessed by Weighted Global Rate, which showed an average of 16,15 (SD = 1,42), the demands that most contribute to fatigue in the workplace are the temporal and mental demands. It is the fact that the operators have a set time to solve problems, thus, need a continuous monitoring of the process has triggered a strong pressure on the environment and thereby causing fatigue to the individuals involved.